Diversity in agricultural research resources in the Asia-Pacific region - Beintema, Nienke M.; Stads, Gert-Jan (International Food Policy Research Institute, 2008)
This report reviews the major investment trends, human resource trends, and institutional developments in public agricultural research and development (R&D) in 11 countries of the Asia-Pacific region, drawing from comprehensive datasets derived from primary surveys. These data are linked with investment and human resources data from the Chinese government and other secondary sources to provide a wider regional and global context for the sample's agricultural R&D investment trends. The Asia-Pacific region is a highly diverse region in terms of geography, population distribution, economic development, and cultural, political, and historic backgrounds. Employing more than 50,000 full-time equivalent (fte) agricultural researchers in 2002, China has the largest agricultural R&D system in the world in terms of number of research staff. But the region also encompasses small Pacific islands with less than 100 fte agricultural researchers each. Average degree levels of agricultural research staff also diverged widely from one country to the other. Nonetheless, all countries in our survey sample experienced improvements in qualification levels of agricultural scientists over the past decade, despite the challenges that certain countries face in rejuvenating their researcher pool. Distribution of spending among countries in the Asia-Pacific region was also very uneven, with China, Japan, and India accounting for the lion's share of the region's agricultural research expenditures. Many countries in the region realized impressive growth in agricultural R&D spending in recent years, whereas growth in other countries was more sluggish (and in some cases negative). Funding for agricultural research is still predominantly through government allocations, although a number of countries now have a dual funding system where a portion of the government allocations are disbursed through a competitive funding system. A number of countries have sought to fund agricultural R&D by a tax on agricultural production or exports while other countries have been successful in commercializing their research results.